Transcriptomic characterization of the dorsal lobes after hepatectomy of the ventral lobe in zebrafish. (December 2015) - Feng, Guohui; Long, Yong; Peng, Jinrong; Li, Qing; Cui, Zongbin
Abstract Background The liver possesses an ability of compensatory growth after removing three of five lobes in mammals or one of three lobes in zebrafish. The reenter of hepatocytes into the cell cycle is one of the hallmarks for the initiation of liver compensatory growth, but cellular and molecular mechanisms underlying the activation of hepatocytes remain largely unknown. Results To better understand the process, transcriptional profiles of the remaining liver dorsal lobes in female zebrafish were generated with RNA-seq. About 44 million raw reads were obtained from three sequencing libraries and 71 % of raw reads were mapped to the reference genome of zebrafish. A total number of 5652 genes were differentially expressed in at least one of two time points during the compensatory growth of liver dorsal lobes and classified into different functional categories. A number of genes encoding angiogenesis-related growth factors/ligands and apoptosis-associated cytokines were strongly expressed at 6-h time point after the removal of the ventral lobe. Gene ontology enrichment analysis of genes up-regulated during early stages of liver compensatory growth revealed that small GTPase-mediated signal transduction, RNA processing and intracellular protein transport were the most highly overrepresented biological processes and SNARE interactions in vesicular transport, proteasome and basal transcription factors were the most highly enriched pathways. Moreover, 477 genes differently expressed during liver compensatory growth of both female zebrafish and mice were involved in the response to stimulus, DNA replication, metabolic processes of fatty acid, lipid and steroid, multicellular organismal homeostasis and extracellular matrix constituent secretion. Conclusions Multiple biological processes and signaling pathways are immediately activated in remaining dorsal lobes of female zebrafish right after removal of the ventral lobe and these findings provide crucial clues for further identification ofcis -elements andtrans -factors that are extensively involved in the initiation of liver compensatory growth.